2023
DOI: 10.3390/ijms24021787
|View full text |Cite
|
Sign up to set email alerts
|

Combined Omics Analysis Further Unveils the Specific Role of Butyrate in Promoting Growth in Early-Weaning Animals

Abstract: Abnormal mutations in the microbial structure of early-weaning mammals are an important cause of enteritis. Based on the multiple known beneficial functions of butyrate, we hypothesized that butyrate would alleviate the imbalance of intestinal homeostasis induced by early weaning in animals. However, the mechanisms of action between butyrate and intestinal microbes are still poorly explored. In this study, we aimed to investigate whether butyrate exerts beneficial effects on the structure of the intestinal flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 103 publications
0
1
0
Order By: Relevance
“…Studies have indicated that the relationship between the host and gut microbiome is mutualistic, with the host provision of hospitable niches and undigested food for the microbiome, and the feedback of these microorganisms with secondary metabolites and neuroactive components ( Mörkl et al, 2020 ; Berding et al, 2021 ; Zhao et al, 2021 ). Recent studies on bidirectional gut–brain interactions have indicated significant regulatory effects on physiological and gastrointestinal homeostatic functions ( Reyer et al, 2018 ; Mayer et al, 2022 ; Zhang et al, 2023 ). Microbiomes, in either the gastrointestinal tract or skin, combined with their metabolites, have been identified as a major source of information signaling, and influenced the central nervous system either directly through systemic circulation or indirectly by interacting with gut-based enteroendocrine cells ( Agirman et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that the relationship between the host and gut microbiome is mutualistic, with the host provision of hospitable niches and undigested food for the microbiome, and the feedback of these microorganisms with secondary metabolites and neuroactive components ( Mörkl et al, 2020 ; Berding et al, 2021 ; Zhao et al, 2021 ). Recent studies on bidirectional gut–brain interactions have indicated significant regulatory effects on physiological and gastrointestinal homeostatic functions ( Reyer et al, 2018 ; Mayer et al, 2022 ; Zhang et al, 2023 ). Microbiomes, in either the gastrointestinal tract or skin, combined with their metabolites, have been identified as a major source of information signaling, and influenced the central nervous system either directly through systemic circulation or indirectly by interacting with gut-based enteroendocrine cells ( Agirman et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%